Comprehensive Evaluation of Reliability of Protection System in Smart Substation - Jipu Gao; Xu He; Peichao Zhang; Changbao Xu (Institute of Advanced Engineering and Science, 2014)
The reliability of smart substations has a great significance on the safety and stability of smart grid operation. Taking the protection system in smart substation as an example, this paper constructs comprehensive reliability models to evaluate the reliability of smart substations with different architectures. The paper first illustrates two important aspects which affect the reliability of the protection system, namely the network architecture and the maintenance strategy. To satisfy these two aspects, the paper then adopt the Monte Carlo simulation combined with the Reliability Block Diagram method to make quantitative reliability analysis. At last, reliability of four power transformer protection systems applying different maintenance strategies with alternative architectures is evaluated. The simulation results show clearly that advanced maintenance strategies such as conditional maintenance will play a critical role in enhancing the reliability and availability of smart substation. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5109